Sensing performance of β-Ga2O3 metal–semiconductor-metal deep ultraviolet photodetectors with refractory TiW electrodes at high temperatures - Maolin Zhang; Wanyu Ma; Zeng Liu; Lili Yang; Shan Li; Yufeng Guo; Weihua Tang (Results in Physics, 2023)
Given the critical impact of high-temperature environments on the detection performance and stability of deep ultraviolet (DUV) photonic devices, especially in urgent demands from fields including high-temperature industries and flame detection, the research on high-temperature resistant DUV photodetectors (PDs) has become of utmost importance. Due to its intrinsic high-temperature resistance, β-Ga2O3 holds significant potential in the field of DUV photodetection under elevated temperature environments. The conventional electrode material, titanium, typically exhibits poor high-temperature performance, while interfaces are susceptible to degradation at elevated temperatures. In this study, we fabricated β-Ga2O3 metal–semiconductor-metal (MSM) PDs using the refractory metal TiW as the electrode, and investigated their DUV detection performance across the temperature range of 300 to 800 K. Favorable performance was achieved at room temperature, with a photo-to-dark current ratio (PDCR) of 3.1 × 106, a responsivity (R) of 0.2 A/W, a detectivity (D*) of 8.3 × 1013 Jones, and an external quantum efficiency (EQE) of 102.3 %. However, an increase in operating temperature led to a continuous rise in dark current (Idark) and a decrease followed by an increase in photocurrent (Iphoto). In an 800 K operating environment, the PDCR decreased to 4.4 × 102, R increased to 0.7 A/W, D* dropped to 2.0 × 1012 Jones, and EQE improved to 343.7 %. Furthermore, the temperature-dependent rise and decay times were investigated, and a detailed analysis of the relevant recombination and transport mechanisms under high-temperature conditions was conducted. By achieving high-performance and stable operation of β-Ga2O3 PDs at 800 K, this study provides prospects for the application of β-Ga2O3 PDs in harsh environments.